Plasticity of the Dorsal “Spatial” Stream in Visually Deprived Individuals - Giulia Dormal; Franco Lepore; Olivier Collignon (Neural Plasticity)
Studies on visually deprived individuals provide one of the most striking demonstrations that the brain is highly plastic and is able to rewire as a function of the sensory input it receives from the environment. In the current paper, we focus on spatial abilities that are typically related to the dorsal visual pathway (i.e., spatial/motion processing). Bringing together evidence from cataract-reversal individuals, early- and late-blind individuals and sight-recovery cases of long-standing blindness, we suggest that the dorsal “spatial” pathway is mostly plastic early in life and is then more resistant to subsequent experience once it is set, highlighting some limits of neuroplasticity.